MycoNews 2020: President’s message, news, reports, awards, personalia, book news, and correspondence - David L. Hawksworth (IMA Fungus)
Abstract This second annual edition of MycoNews starts with a message from IMA President Wieland Meyer regarding the steps being taken to legally incorporate the Association in Switzerland. News is provided on progress in the arrangements for IMC12 (Amsterdam 2022), release of the State of World’s Plants and Fungi report, mycology under the Coronavirus pandemic, and two new biodiversity initiatives in The Netherlands. Reports are presented from the: 1st International Symposium on Tropical African Mycology (Benin 2019); Recent Advances in the Biodiversity, Biology, and Biotechnology of Fungi (Pondicherry 2019); the 4th International Malassezia Workshop (virtual 2020); Dutch Design Week (2020), and UK Fungus Day (2020). An honour awarded to Francis Martin is recorded. Birthday greetings from IMA go to John Walker, José Dianese, Richard Harris, Tomasz Majewski, David Malloch, and John Sheard. Tributes are paid to the passing of John Peberdy, Anthony Trinci, and Balamuri Vittal. This contribution continues with news of 10 new mycological books published in 2019 or 2020 and concludes with a letter on the appropriateness of adopting the term ‘Funga’.